2007
DOI: 10.1007/bf03325963
|View full text |Cite
|
Sign up to set email alerts
|

Removal of lead from aqueous solution using low cost abundantly available adsorbents

Abstract: ABSTRACT:The removal of poisonous Pb (II) from wastewater by different low-cost abundant adsorbents was investigated. Rice husks, maize cobs and sawdust, were used at different adsorbent/metal ion ratios. The influence of pH, contact time, metal concentration, adsorbent concentration on the selectivity and sensitivity of the removal process was investigated. The adsorption efficiencies were found to be pH dependent, increasing by increasing the solution pH in the range from 2.5 to 6.5. The equilibrium time was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(97 citation statements)
references
References 11 publications
5
92
0
Order By: Relevance
“…This can be attributed to the effect of pH on affinity between adsorbent (biochar) and adsorbate (metal ion solution) and the speciation of metals and dissociation of active functional sites on the adsorbent [15]. At low pH, the surface functional groups (mainly oxygen-containing groups) linked to the H + ion making competition between Ni 2+ ions and H + ions which resulted in a lower electrostatic repulsion [16]. Similar findings were observed .ÕOÕo HW DO [17] for almond shell biochar who reported that maximum adsorption of Ni 2+ occurred around pH 7.…”
Section: Effect Of Solution Ph On Ni 2+ Adsorptionmentioning
confidence: 99%
“…This can be attributed to the effect of pH on affinity between adsorbent (biochar) and adsorbate (metal ion solution) and the speciation of metals and dissociation of active functional sites on the adsorbent [15]. At low pH, the surface functional groups (mainly oxygen-containing groups) linked to the H + ion making competition between Ni 2+ ions and H + ions which resulted in a lower electrostatic repulsion [16]. Similar findings were observed .ÕOÕo HW DO [17] for almond shell biochar who reported that maximum adsorption of Ni 2+ occurred around pH 7.…”
Section: Effect Of Solution Ph On Ni 2+ Adsorptionmentioning
confidence: 99%
“…The management of spent primary and secondary batteries has been an issue of environmental concern in developing countries especially considering the absence of basic waste collection and management infrastructure (Zabaniotou et al, 1999;Aktas et al, 2004;Nnorom and Osibanjo, 2006a;Abdel-Ghani et al, 2007;Daryabeigi Zand and Abduli, 2008;Rabah et al, 2008). Batteries represent a large volume of toxic and hazardous materials in common use (Lankey and McMicheal, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there is a trend to use the alternative and low-cost materials for arsenic removal from the waters in laboratory or medium-scale experiments. Effectiveness of chemically modified or native biomass in processes of arsenic removal was evaluated and proved by various authors (Abdel-Ghani et al, 2007;Boddu et al, 2008;Cernansky et al, 2007;Loukidou et al, 2003;Malakootian et al, 2009;Murugesan et al, 2006;Rahaman et al, 2008;Seki et al, 2005).…”
Section: Introductionmentioning
confidence: 99%